Konsep Ta'abbudi Dan Ta'aqquli Dan Implikasinya Terhadap Perkembangan Hukum Islam - Jamaa, La (UIN Sunan Kalijaga, 2013)
The concept ta’abbudirelating to matters of worship ma?dah, and ta’aqqulirelating to the affairs and worship gairu ma?dah. Ta’abbudiabsolute, static, and its existence is not based on mere outward benefit, while ta’aqquliis relative, not static, and its existence is based on the benefit to humans so it is rational. However, in each ta’aqqulidefinitely embodied the values of worship. Instead, at each contained ta’abbudialso for human benefit. Both of these concepts have great contribution in the development of Islamic law.